DAMPAK â€œBEDOL DESOâ€ TERHADAP MEDIA DAKWAH PENDEKATAN KOMUNIKASI BUDAYA DI DESA GIRI PURNO, TEBO, JAMBI - anshori, muhammad; januri, januri; rosyidi, Andri (INTERCODE, 2024)
Giri Purno Village "GIRI" means originally from Wonogiri "PURNO" means Perfect, so Giri Purno means the Community from Wonogiri that is Perfect. the Bedol Deso program, some residents were eventually sent to the island of Sumatra as a form of population transmigration, specifically placed in the province of Jambi, Bungo Tebo district, Rimbo Ilir sub-district, Giri Purno village. The community of Giri Purno Village mostly earns a living as farmers, with the majority of the population being Javanese, in addition to the Minangkabau, Malay, and Batak ethnic groups. Living side by side in harmony among neighbors and sharing the same situation as transmigrants, who are referred to as migrants and reside in another area. Keywords: Giri Purno Village, The Bedol Deso, The community